Pengaruh Kompetensi, Independensi, Emotional Quotient dan Audit Tenure terhadap Kualitas Audit (Studi Empiris pada Auditor di Kantor Akuntan Publik Riau dan Kepulauan Riau) - Nugraha Tasya Ramadhanty; Hardi; Meilda Wiguna (Jurnal Kajian Akuntansi dan Auditing, 2019)
This study aims to test and empirically prove the effect of competence, independence, emotional quotient, and audit tenure on audit quality. The sample of this study was 45 auditors from 15 public accounting firms in Riau and Riau Islands. The method of analysis in this research is multiple linear regression analysis. The results showed that (1) Competence has a positive effect on Audit Quality (2) Independence has a positive effect on Audit Quality (3) Emotional Quotient has a positive effect on audit quality (4) Audit Tenure has a negative effect on Audit Quality.